Impactos que dificultan la práctica de turismo sostenible en la ciudad de Iquitos, 2019 - Flores Doñe, Claudia Sarita (2021)
The study was carried out with the purpose of analyzing the urban impacts that hinder the practice of sustainable tourism in the city of Iquitos, Peru in 2019. A descriptive, quantitative, cross-sectional and observational design was applied, the population of which was made up the streets, shreds, avenues, green areas, park and gardens of the city center of Iquitos. The sample was 30 observations made to the places determined in the sampling frame. The required ethics have been met. The research objectives have been met, obtaining the urban planning impacts: ecological (soil, vegetation, landscape, animals), the city (over dimensioning, green areas, urbanizations, cleaning and others, from pollution (solid waste, landscape, acoustics, spaces) and the sociological (acculturation, behavior of people and social networks). The hypothesis has been demonstrated arriving at the conclusion that the ecological, urban, pollution and sociological impacts hinder the practice of sustainable tourism in the city of Iquitos, then, because statistically they are evaluated moderately with a tendency to be high urban impacts.